Ensaios em Macroeconomia: política monetária, gerenciamento da dívida pública, multiplicadores fiscais e incerteza macroeconômica - Nobrega, Wellington Charles Lacerda (2020)
Chapter 1 – Public Debt Management and the Interaction Between Monetary and Fiscal Policies: A DSGE model for the Brazilian’s Economy The first essay uses a DSGE model to investigate the effects of the public debt average maturity management over both public debt and economic cycle dynamics. The model developed is based on Krause and Moyen (2016) and includes short and long-term versions for bonds and interest rate. Three management scenarios are evalueted, including brazilian securities average term. The main findings of the developed model suggests a considerable influence of public debt average maturity policies over fiscal and monetary variables, highlightning that in short-term oriented model, the contracionary monetary policy shock lead to a procyclical effect in debt trajectory, what may turn public debt evolution unsustainable under this circustances. Chapter 2 – Government Fiscal Multipliers of Spending and Investiment In Long-Term Debt Presence The second essay investigates the relationship between fiscal multipliers of spending and investment in long-term bonds presence and assesses the influence of average maturity of public debt over fiscal policy efficiency. For this, a large scale DSGE model for an open economy addapted to the characteristics of brazilian economy was developed. In general, the results suggests a superiority of fiscal policies based in public investment relatively to consumption fiscal policy, according to Cavalcanti and Vereda (2015) and Moura (2015). Furthermore, the model was able to identify two kinds of crowding-out effects due to public spending arise. In the first scenario, it was verified the well known crowding-out effect over private investment; in the second case, it was observed a effect over public spending components due to long-run balanced budget constrained hyphotesis. Finally, the results also shows that a suitable public debt management policy has positive effects over the fiscal multiplier causing lower response of long-term interest rate and then a higher multiplier due to a fiscal expansion to both public investment and consumption, the higher is the average maturity of public bonds.Chapter 3 – Measuring Macroeconomic Uncertainty: A Textual Sentiment Analysis of Brazilian Public Debt Reports Lastly, the third essay sought to measure macroeconic unvertainty through Textual Sentiment Analysis of Brazilian Public Debt Reports. Fistly, it is developed a specific dictionary related to public debt context then it is used for parametrization of a Macroeconomic Uncertainty Index (MUI). After, a DSGE model is developed in order to derive the structural relationships of an economy facing a macroeconomic uncertainy shock. From there, the structural results are used as foundation for a empirical investigation of uncertainty effects over macroeconomics variables through a Vectors Autorregressive approach using sign agnostic identification as proposed by Uhlig (2005). The results shows that the developed index resembles those already existing for the Brazilian economy. Furthermore, the uncertainty sentiment derived from the fiscal documents was able to replicate the contractionists effects suggested by economic theory